Ecological and Morphological Differentiation Among COI Haplotype Groups in the Plant Parasitic Nematode Species Mesocriconema Xenoplax - Matczyszyn, Julianne N (Journal of nematology, 2022)
© 2022 Julianne N. Matczyszyn et al., published by Sciendo.